Physicochemical Properties of Honey from Contract Beekeepers, Street Vendors and Branded Honey in Sabah, Malaysia - Robin Lim A H; Lum Mok Sam; Januarius Gobilik; Jamilah Lee Nyuk Choon; Kimberly Ador; Jonal Majampan; Suzan Benedick (Tropical Life Sciences Research, 2022)
The chemical properties of honey depend on the source of collection to packaging, but little is known about honey in Sabah. The aim of this study was to distinguish between the physicochemical properties and mineral content of 76 honey samples from local sources and supermarkets in Sabah, which were from contract beekeepers, unknown sources and branded honey. Raw honey was collected from contract beekeepers, while honey from unknown source was obtained from street vendors and wet markets, while branded honey was purchased from local supermarkets. The chemical parameters of the honey were assessed using established methods, while the mineral content of the honey was determined using inductively coupled plasma optical emission spectroscopy (ICP-OES). Significant differences were found in several parameters measured in honey from different sources, with principal component analysis (PCA) showing clear separation between the measured parameters, yielding five factors that accounted for up to 72.25% of the total explained variance. Honey from contract beekeepers showed significant differences and higher mineral content (Ca, Cu, Fe, K, Mg, Na and Zn) compared to honey from unknown source and branded honey. Potassium was the most important element in the study with an average of 2.65 g/kg and 629.4 mg/kg for sources from contract beekeepers and branded honey, respectively. The honey from the contract beekeepers was of better quality due to its high mineral content. The results suggest that honey from contract beekeepers could be a good choice when it comes to high mineral content. Sifat kimia madu adalah bergantung kepada sumber pengumpulan hingga ke peringkat pembungkusan, namun demikian, maklumat tentang madu di Sabah kurang diketahui. Matlamat kajian ini adalah untuk membezakan antara sifat fizikokimia dan kandungan mineral bagi 76 sampel madu daripada sumber tempatan dan pasar raya di Sabah, iaitu daripada penternak lebah kontrak, sumber yang tidak diketahui dan madu berjenama. Madu mentah diperoleh daripada penternak lebah kontrak, manakala madu daripada sumber yang tidak diketahui telah diperoleh daripada peniaga jalanan dan pasar basah, manakala madu berjenama dibeli dari pasar raya tempatan. Parameter kimia madu dinilai menggunakan kaedah sedia ada yang telah ditetapkan, manakala kandungan mineral madu ditentukan menggunakan inductively coupled plasma optical emission spectroscopy (ICP-OES). Terdapat perbezaan bererti bagi beberapa parameter yang diukur dalam madu daripada sumber yang berbeza dan analisis komponen utama (PCA) menunjukkan perbezaan yang jelas antara parameter yang diukur, menghasilkan lima faktor yang menyumbang sehingga 72.25% daripada jumlah varians yang dijelaskan. Madu dari penternak lebah kontrak menunjukkan perbezaan yang ketara dan kandungan mineral yang lebih tinggi (Ca, Cu, Fe, K, Mg, Na dan Zn) berbanding madu dari sumber yang tidak diketahui dan madu berjenama. Kalium merupakan unsur terpenting dalam kajian dengan purata 2.65 g/kg dan 629.4 mg/kg masing-masing untuk sumber daripada penternak lebah kontrak dan madu berjenama. Madu dari penternak lebah kontrak adalah lebih berkualiti kerana kandungan mineralnya yang tinggi. Keputusan menunjukkan bahawa madu daripada penternak lebah kontrak boleh menjadi pilihan yang baik kerana ia mempunyai kandungan mineral yang tinggi.